Extending writing instruction beyond school walls - Arslan, Recep Şahin; Kızıl, Aysel Şahin (My University, 2007)
Perceived, until recently, as a powerful research and communication tool, the internet with new web publication systems has manifested itself as more than just a readable and searchable device. By changing the role of the users from simply readers into writers on the web, publishing opportunities have been redefining ways of using the internet in language teaching as well (Richardson, 2004). One of the applications redefining the place of the web in language education is what is called weblogs. This paper discusses weblog use in language teaching with a focus on what weblog offers in writing instruction.
Bildiri - Yayımlanmış
Keywords: Blog; Weblog; Writing instruction; English as a foreign language